Preparation and Characterization of Sodium Alginate-Based Oxidized Multi-Walled Carbon Nanotubes Hydrogel Nanocomposite and its Adsorption Behaviour for Methylene Blue Dye - Makhado, Edwin; Hato, Mpitloane Joseph (Frontiers in Chemistry, 2021)
Herein, a sodium alginate/poly (acrylic acid)/oxidized-multi-walled carbon nanotubes hydrogel nanocomposite (SA/p(AAc)/o-MWCNTs HNC) was synthesized by in situ free-radical polymerization method. The synthesized SA/p(AAc)/o-MWCNTs HNC was used to remove methylene blue (MB) blue from aqueous solution. The prepared SA/p(AAc)/o-MWCNTs HNC was confirmed by employing various characterization techniques such as Fourier transform infrared, Raman, X-ray diffraction, scanning/transmission, thermogravimetric analysis and dynamic mechanical analysis. The SA/p(AAc)/o-MWCNTs HNC exhibited a maximum swelling ability of 2265.4 % at pH 9.0. In the sorption process, the influence of vital parameters including the initial pH, adsorption dose, contact time and concentration were systematically examined on a batch mode. Subsequently, adsorption kinetics and adsorption isotherm models were employed to assess the nature and mechanism of the adsorption process. Adsorption kinetics were best described by pseudo-second-order model, while the Langmuir isotherm model governed the adsorption isotherm. The SA/p(AAc)/o-MWCNTs HNC exhibited a maximum adsorption capacity of 1596.0 mg/g at 25 °C. This adsorbent showed excellent MB uptake and good regeneration ability.